The Effectiveness of Sensory Flashcard Media and Classification on Knowledge of Fruit and Vegetable Consumption among Sixth-Grade Students - Istiqomah Islamiah J. Potale; Sunarto Kadir; Laksmyn Kadir (Indonesian Journal of Global Health Research, 2026)
Fruits contain a broad range of essential nutrients, including proteins, fats, and carbohydrates, while vegetables serve as vital plant-based foods that help meet daily nutritional needs. Gorontalo Province is among the regions in Indonesia with the lowest fruit and vegetable intake, with 92.5% of the population not meeting the recommended ≥5 servings per day. This study aimed to assess the effectiveness of flashcard-based education in improving knowledge of fruit and vegetable consumption among sixth-grade students at State Elementary School 59, East Gorontalo City. This research employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. A total of 35 sixth-grade students were selected through purposive sampling. Research instruments included a closed-ended questionnaire with structured items and predetermined response options. Prior to data collection, the questionnaire underwent validity testing using Spearman’s rank correlation, where items with r-count > r-table (p < 0.05) were considered valid. Reliability testing was conducted using Cronbach’s Alpha, and all constructs achieved coefficients ≥ 0.70, indicating acceptable internal consistency. Data were analyzed using the Wilcoxon test, followed by the Kruskal–Wallis test with Post Hoc analysis. The results showed a significant improvement in students’ knowledge after the flashcard educational intervention, with a p-value of 0.000. Interactive learning media such as flashcards enhanced students’ engagement, concentration, and comprehension, enabling them to better understand the nutritional benefits of fruits and vegetables through play-based learning activities. Flashcard-based education is effective in increasing students’ knowledge of fruit and vegetable consumption and serves as an engaging learning tool to support nutritional education in schools.